STRATEGI PENGEMBANGAN DAN PENGELOLAAN UMKM MELALUI PROSES DIGITALISASI DI DESA BURANGKENG BEKASI TIMUR - Purnamasari, Pupung; Citra N., Anggelia; Ismaya, Cahya; Khalishah Saharani Effendi, Zhafirah (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The role of digital technology such as the internet or artificial intelligence (AI) in increasing economic growth, especially for businesses that are still pioneering such as MSMEs or micro, small and medium enterprises, as well as encouraging the creation of innovation in creating businesses. Apart from increasing innovation and business productivity, this technology can also open up new opportunities for economic growth by creating new markets and business models, as well as access to information and services that have a wider reach. MSMEs or micro, Small and medium enterprises are productive businesses owned by individuals or business entities that meet the criteria for being a micro enterprise. More clearly, the definition of MSME sis regulated in law of the Republic of Indonesia No. 20 of 2008 concerning MSMEs. The law states that MSMEs are based on the type of business, namely micro businesses, small businesses and medium businesses. Type of MSMEs include MSMEs in the fashion sector, and others. MSMEs can also be a solution for beginners to start a business and earn income. For example, there are MSMEs in Burangkeng village, there are many MSMEs of various types available. However, there are still many MSMEs players who do not understand how to properly manage and develop MSMEs. Our activities are aimed at helping MSMEs manage and develop their business to attarct the attention of consumers, With this activity, it is hoped that it can help MSMEs develop their businesses by utilizing digital technology which is very influential in marketing a business in today's digital era. We help in this matter because there are some people who do not yet understand the use of technology in the business sector.